2020
DOI: 10.9734/jabb/2020/v23i130136
|View full text |Cite
|
Sign up to set email alerts
|

EFVb-HAART Increases Mortality, Locomotor Deficits and Reduces Reproductive Capacity in Drosophila melanogaster

Abstract: Aims:This study was designed to evaluate the effects of Efavirenz-based highly active antiretroviral therapy (EFV b -HAART, Efavirenz/Lamivudine/Tenofovir) with emphasis on survival, longevity, climbing ability, and reproductive capacity in D. melanogaster. Methods: The experiments were carried out at the Africa Center of Excellence in Phytomedicine Research and Development (ACEPRD), University of Jos, Nigeria between January 2017 and August 2018. D. melanogaster (both sexes) 1-4 days old were exposed to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Nevertheless, HAART induces oxidative stress [2,3,4] and life expectancy in HAART treated HIV patients is shorter than the uninfected population [3]. Recently, Iorjiim et al [5] reported that D. melanogaster exposed to EFV b -HAART developed locomotor deficits, decreased lifespan as well as reproductive capacity, and hypothesized that these observations might partly be oxidative stress-related toxicities. Therefore, this study aims to evaluate the toxicological impact of EFV b -HAART on total protein, some antioxidants parameters (total thiols, Glutathione-S-transferase (GST), Catalase (CAT), Superoxide dismutase (SOD) and Malondialdehyde (MDA) levels (as a measure of free radical generation) in D. melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, HAART induces oxidative stress [2,3,4] and life expectancy in HAART treated HIV patients is shorter than the uninfected population [3]. Recently, Iorjiim et al [5] reported that D. melanogaster exposed to EFV b -HAART developed locomotor deficits, decreased lifespan as well as reproductive capacity, and hypothesized that these observations might partly be oxidative stress-related toxicities. Therefore, this study aims to evaluate the toxicological impact of EFV b -HAART on total protein, some antioxidants parameters (total thiols, Glutathione-S-transferase (GST), Catalase (CAT), Superoxide dismutase (SOD) and Malondialdehyde (MDA) levels (as a measure of free radical generation) in D. melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…Colpo et al [35] observed similar findings in Drosophila treated with Ilex paraquariensis post feed on high-fat diet. The choice of 7 days treatment period was appropriate as greater than 95 % of the fly population were alive on the seventh day [36].…”
Section: Discussionmentioning
confidence: 99%
“…The D. melanogaster (Harwich strain) was sourced at the ACEPRD, University of Jos. The fly stock was inbred and maintained at standard environmental conditions, as previously described [20]. The flies were fed on Drosophila food composed of yellow cornmeal (100 g), brewer's yeast (20 g), agar (16 g), and the preservative methylparaben (1 g) [25].…”
Section: Animal Modelmentioning
confidence: 99%
“…HAART drug-related ADRs include nausea, vomiting, and skin eruptions [4]. Other severe ADRs associated with HAART include induction of free radicals (reactive oxygen and nitrogen species, RONS) [18,19], reduced reproductive capacity [1,20], neurodegenerative diseases [21], and accelerated aging [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation